2021
DOI: 10.1002/ffj.3657
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the chemical composition of six essential oils with mass spectroscopy and evaluation of their antibacterial and antioxidant potential

Abstract: This study determined the chemical composition of Cinnamomum verum J.Presl, Cistus ladaniferus L., Laurus nobilis L., Senecio anteuphorbuim, Boswellia serrata Roxb. ex Colebr. and Schinus molle L. essential oils (EOs) by gas chromatography‐mass spectrometry. Moreover, the six EOs were screened in order to reveal their antibacterial and antioxidant activities. They were initially tested against six pathogenic bacteria: Staphylococcus aureus (MRSA: methicillin‐resistant Staphylococcus aureus), Escherichia coli (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…Further proof of the antimicrobial potential of this molecule was given by Dalli et al [ 82 ], testing Nigella sativa seed EO against different bacterial strains, and obtaining promising results against Acinetobacter baumannii . Irahal et al [ 41 ] tested the EO extracted from S. molle and it showed an MIC against Staphylococcus aureus of 0.25 mg/mL. Finally, Lisboa et al [ 83 ] found that the EO from Rosmarinus officinalis (alpha-phellandrene 11.1%) could be considered as a potential treatment against endometritis-causing microorganisms in mares.…”
Section: Resultsmentioning
confidence: 99%
“…Further proof of the antimicrobial potential of this molecule was given by Dalli et al [ 82 ], testing Nigella sativa seed EO against different bacterial strains, and obtaining promising results against Acinetobacter baumannii . Irahal et al [ 41 ] tested the EO extracted from S. molle and it showed an MIC against Staphylococcus aureus of 0.25 mg/mL. Finally, Lisboa et al [ 83 ] found that the EO from Rosmarinus officinalis (alpha-phellandrene 11.1%) could be considered as a potential treatment against endometritis-causing microorganisms in mares.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the EOs were effective on both gram-positive and gram-negative bacterial pathogens, as shown clearly in the results of the microdilution assay. Eugenol, linalool, α-terpineol, thymol, 1,8-cineole, camphor, and carvacrol are among the bioactive components, which have prominent inhibitory effect against bacteria (26). This broad range of compounds in EOs make their antibacterial activity not reliant on one specific mode of action; they exhibit various mechanisms and can attack several targets in a cell to inactivate the bacterium (27).…”
Section: Discussionmentioning
confidence: 99%
“…5 Different environmental and genetic factors, chemotypes, and the nutritional status of the plants can all contribute to the observed differences in the constituents of basil EO across countries. 36,37 Antioxidant activities of S.…”
Section: Chemical Composition Of Extracts and Eomentioning
confidence: 99%